Effect of activated carbon to the structural properties of copper zinc ferrite prepared via mechanosynthesis - Noor Syafiqah, Hassin (2016)
In this research, copper zinc ferrite nanoparticles, Cu0.2Zn0.8Fe2O4 were successfully produced by mechanosynthesis method. Cu0.2Zn0.8Fe2O4 nanoparticle precursor were produced dried Fe2O3, CuO and ZnO were mixed with a molar ratio of 1:0.1:0.4 to form the mixture. After ball milled for 8 hours at 600 rpm with ball to powder ratio of 10:1, the brownish powder of copper zinc ferrite nanoparticles, dried at 120 °C in air and then were calcined at 750 °C for an hour. The activated carbon were produced from sawdust via pyrolysis method using nitrogen gas. Copper zinc ferrite nanoparticles were added with activated carbon with four different weight percentage of copper zinc ferrite and activated carbon and then were mixed homogenously by sol-gel method with the presence of absolute ethanol as fuel. The amorphous precursor of carbon copper zinc ferrite then characterized by Fourier Transform Infrared Spectroscopy (FTIR) Study , X-Ray Powder Diffraction (XRD) Analysis and Scanning Electron Microscopy (SEM) for the structural measurement of carbon copper zinc ferrite nanoparticle. The effect of activated carbon to the Cu0.2Zn0.8Fe2O4 were investigated. It was found that the activated carbon does not interrupt the magnetic properties of the Cu0.2Zn0.8Fe2O4 but the structure of the magnetite become lighter and more porous as the percentage weight of carbon is increasing. From the XRD data, at the weight percentage of 40%wt of Cu0.2Zn0.8Fe2O4 and 60% wt of activated carbon, the peak of magnetite at (3 1 1) was the highest and most sharp. Proving the by adding carbon to the copper zinc ferrite with that respective percentage weight does not affect the properties of copper zinc ferrite but does affect its structure.